Power Analysis Of A 100 Watt Micro Hydro Power Generator Using An Internet Of Things (IoT) Web Services Based On The Code Igniter Framework - Yudhis Thiro Kabul Yunior; Hartono Hartono; Slamet Hariyadi; Dwiyanto Dwiyanto; Tekat Sukomardojo; Surya Widdana (Universitas Dharma Wacana, 2025)
Small-scale Microhydro power plants (100 Watt) require a real-time and accurate power monitoring system to improve efficiency and maintenance. This research aims to develop an Internet of Things (IoT)-based electrical power analysis system by utilizing a Web Service based on the CodeIgniter Framework to process and display data online. The system consists of sensor modules (voltage and current) using ZMPT101B and ACS712, an ESP32 microcontroller for data transmission, and a CodeIgniter backend that provides a RESTful API for data storage and processing. Power (P), voltage (V), current (I), and energy (kWh) data are displayed on a web dashboard with graphic visualization using Chart.js. The research method uses a Research and Development (R&D) approach with stages of needs analysis, system design, implementation, and testing. The test results show that the system is able to monitor power with 95% accuracy compared to digital multimeter measurements, and has a data transmission latency of <2 seconds. This solution can be applied to small-scale Microhydro power plants for IoT-based monitoring with low cost and high scalability.